2015
DOI: 10.1021/acsnano.5b04501
|View full text |Cite
|
Sign up to set email alerts
|

A Near-Infrared Triggered Nanophotosensitizer Inducing Domino Effect on Mitochondrial Reactive Oxygen Species Burst for Cancer Therapy

Abstract: Photodynamic therapy (PDT) is a well-established modality for cancer therapy, which locally kills cancer cells when light irradiates a photosensitizer. However, conventional PDT is often limited by the extremely short lifespan and severely limited diffusion distance of reactive oxygen species (ROS) generated by photosensitizer, as well as the penetration depth of visible light activation. Here, we develop a near-infrared (NIR) triggered nanophotosensitizer based on mitochondria targeted titanium dioxide-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
174
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(180 citation statements)
references
References 58 publications
3
174
0
3
Order By: Relevance
“…Moreover, an in vivo study confirmed this observation showing that different shapes of silica NPs differentially altered physiological functions in exposed rats (Li et al 2015). We also showed that a minimal intracellular content of titanium is necessary and mandatory to induce a marked calcium homeostasis alteration, which is also cell-type dependent.…”
Section: )supporting
confidence: 78%
“…Moreover, an in vivo study confirmed this observation showing that different shapes of silica NPs differentially altered physiological functions in exposed rats (Li et al 2015). We also showed that a minimal intracellular content of titanium is necessary and mandatory to induce a marked calcium homeostasis alteration, which is also cell-type dependent.…”
Section: )supporting
confidence: 78%
“…Therefore, UCNP-based PDT gains enhanced effectiveness in the eradication of deeper depths tumor cells [195]. This finding has been confirmed both in vitro, in human cancer cells (HeLa and MCF-7 lines) and in vivo, in female Balb/c nude mice [196, 197]. …”
Section: Reviewmentioning
confidence: 87%
“…Due to the short lifetime (<0.1ms) and small diffusion radius of ROS (<20 nm) in biological systems 9, the photosensitizer should be spatially close to the targeted site of action in photodynamic therapy. Mitochondria are key organelles for respiration and the primary source, approximately up to 90%, of cellular ROS generation 10-12. Hence, the mitochondria-targeting nanoparticles loaded with photosensitizers can perturb ROS homeostasis and further induce cell apoptosis, which can achieve maximized photodynamic therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%